DETERMINATION OF TOTAL PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF DICHROSTACHYS CINERA, GUIERA SENEGALENSIS AND VITEX DONIANA - Abubakr, Mohamed; Babiker, Mahomed Osman; Sirag, Nizar; abdAlla, N. (Gezira Journal of Engineering and Applied Sciences, 2018)
The present work was undertaken to determine the phenolic content and antioxidant capacity of three plants used in Sudanese folk medicine. The total phenolic content was measured by Folin Ciocalteau method using gallic acid as standard while the antioxidant capacity was based on the ability of these plant extracts to scavenge DPPH radical. High total phenolic content was detected in Dichrostachys cinera followed by Guiera senegalensis and Vitex doniana. Dichrostachys cinera exhibited the strongest antioxidant capacity with EC50 6.63 μg/ml, followed by Guiera senegalensis (7.74 μg/ml) and Vitex doniana (22.72 μg/ml). A significant linear correlation between total phenolic content and antioxidant capacity(R2=0.9957) confirmed that the phenolic phytoconstituents are responsible for the antioxidant activity. It can be concluded that the three surveyed plants could be potential sources of antioxidant agents